Sapiens. In the path of the human being - Jordi Agustí (Mètode Science Studies Journal: Annual Review)
Despite the disorientation caused by the almost continuous bombardment of news about the discovery of a new fossil that revolutionises everything we knew about human evolution, at the beginning of the twenty-first century, there is a broad consensus on certain key moments in our evolution: from the first clearly bipedal hominines, about 4 million years ago, to the origin of our own species, Homo sapiens, around 300,000 years ago. This consensus on the broad lines of our evolution, however, does not preclude a considerable number of unanswered questions and uncertainties, which are still under discussion today.